Safety of bioabsorbable implants in vitro. Issue 1 (December 2015) - Isyar, Mehmet; Yilmaz, Ibrahim; Nusran, Gurdal; Guler, Olcay; Yalcin, Sercan; Mahirogullari, Mahir
Abstract Background The aim of the present study was to investigate the safety of bioabsorbable plates and screws in humans. Methods For this purpose, an implant system based on [poly(lactic-co-glycolic acids)(85:15)] was designed. The system was tested for pH, temperature, and swelling and then its surface morphology was analyzed for surface porosity using environmental electron microscopy. Then, the effects of this bioabsorbable system on the viability and profileration of osteocytes were examined on a molecular level via in vitro experiments. A [poly(lactic-co-glycolic acids)(90:10)] bioabsorbable implant, which is commercially available and used in orthopedic surgery, was used as control group. For the statistical evaluation of the data obtained in the present study, the groups were compared by Tukey HSD test following ANOVA. The significance level was set asp < 0.05. Results It was observed that the osteocytes cultivated on the PLGA system designed in the present study included more live cells and allowed more proliferation compared to the control. Conclusion One of the criteria in the selection of implants for orthopedic surgery is that a good implant should not need removal and thus a second surgery. In the present study, a bioabsorbable implant was designed considering this criterion. The present study is the first step to prove the safety of this new design by in vitro toxicity and viability experiments.